To what extent are Arab pilgrims to Makkah aware of the middle east respiratory syndrome coronavirus and the precautions against it? - Meshaal S Alotaibi; Abdulaziz M Alsubaie; Khaled A Almohaimede; Turki A Alotaibi; Omar A Alharbi; Abdulrahman F Aljadoa; Abdulaziz H Alhamad; Mazin Barry (Wolters Kluwer Medknow Publications, 2017)
BACKGROUND: Approximately, 80% of the many cases of the Middle East respiratory syndrome coronavirus (MERS-CoV) confirmed worldwide were diagnosed in the Kingdom of Saudi Arabia (KSA). The risk of the disease spreading internationally is especially worrying given the role of KSA as the home of the most important Islamic pilgrimage sites. This means the need to assess Arab pilgrims' awareness of MERS-CoV is of paramount importance. MATERIALS AND METHODS: A cross-sectional study was carried out during Ramadan 2015 in the Holy Mosque in Makkah, Saudi Arabia. Self-administered questionnaires were distributed to 417 Arab participants at King Fahad Extension, King Abdullah Prayer Extension and, King Abdullah Piazza Extension after Taraweeh and Fajr prayers. RESULTS: The mean MERS-CoV knowledge score was 52.56. Majority of the respondents (91.3%) were familiar with MERS-CoV. Saudis had significantly higher knowledge of MERS-CoV than non-Saudis (56.92 ± 18.55 vs. 44.91 ± 25.46, p = 0.001). Females had significantly more knowledge about consanguineous MERS-CoV than males (55.82 ± 19.35 vs. 49.93 ± 23.66, p = 0.006). The average knowledge was significantly higher in respondents who had received health advice on MERS-CoV (56.08 ± 20.86 vs. 50.65 ± 22.51, p = 0.024). With respect to stepwise linear regression, knowledge of MERS-CoV tended to increase by 14.23 (B = 14.23%, p = 0.001) in participants who were familiar with MERS-CoV, and by 8.50 (B = 8.50, p = 0.001) in those who perceived MERS-CoV as a very serious disease. CONCLUSION: There is a great need for educational programs to increase awareness about MERS-CoV.